Study of magnetic field dependent viscosity on a soret driven ferrothermohaline convection in a rotating porous medium - Hemalatha, Raavi (Zielona Góra: Uniwersytet Zielonogórski)
The effect of a magnetic field dependent viscosity on a Soret driven ferro thermohaline convection in a rotating porous medium has been investigated using the linear stability analysis. The normal mode technique is applied. A wide range of values of the Soret parameter, magnetization parameter, the magnetic field dependent viscosity, Taylor number and the permeability of porous medium have been considered.
Keywords: Soret parameter; field dependent viscosity; oscillatory instability; linear stability; Taylor number; permeability of porous medium